Happy hippo, angry duck : 3a book of moods - Boynton, Sandra (New York : Little Simon, 2011)
Animals display emotions from the confused cow to the angry duck.
On board pages.
"9 classic Boynton board books"--P. [4] of cover.
Keywords: Animals -- Juvenile fiction; Emotions -- Juvenile fiction